Quantifying fluid retention following modern pain management in TKA: an observational study - Parkpoom Somrak; Aree Tanavalee; Srihatach Ngarmukos; Chotetawan Tanavalee; Chavarin Amarase; Nonn Jaruthien; Wirinaree Kampitak (Knee Surgery & Related Research)
Abstract Background Body fluid retention after major surgeries, including total knee arthroplasty (TKA), is well documented in the literature. Currently, multimodal pain control protocols consisting of several medications together with early discharge protocol may magnify this adverse event after a patient’s discharge. However, no study has focused on the quantitative and chronological changes in body fluids following modern pain management protocols for TKA. The aim of this study was to investigate the perioperative total body water (TBW) change in patient undergoing TKA. Patients and methods A consecutive series of 85 patients undergoing primary unilateral TKA, with uniform hospital admission, multimodal pain control, and rehabilitation protocol, had five consecutive multifrequency bioelectrical impedance analysis (BIA) scans; baseline, postoperative day 1 (POD 1), postoperative day 3 (POD 3), 2 weeks, and 6 weeks. Changes in TBW, body weight, corticosteroid-fluid retention dose–response relationship, and complications were evaluated. Results Seventy patients completed all five scans and follow-ups. Female patients were dominant, with a mean age of 69.5 years. There were no perioperative complications. At 24 h, the mean total fluid input and output were 3695.14 mL and 1983.43 mL, respectively, with 1711.71 mL increments and a mean accumulative dosage of dexamethasone of 15.14 mg. The mean TBW increased by 2.61 L on POD 1 and continued to peak at 3.2 L on POD 3, then gradually decreased at 2 weeks and reached the baseline level at 6 weeks postoperatively. Similarly, the mean body weight increased to 2.8 kg on POD 1, reached the maximum point at 3.42 kg on POD 3, and returned to baseline at 6 weeks. Conclusions Fluid retention following multimodal pain control in TKA increased from POD 1, peaked on POD 3, and gradually returned to the baseline at 6 weeks. With early discharge protocol, patient education regarding fluid retention after discharge should be considered.